Lepton flavor violating Higgs couplings and single production of the Higgs boson via eγ collision. (8th June 2015) - Yue, Chong-Xing; Pang, Cong; Guo, Yu-Chen
Abstract: Taking into account the constraints on the lepton flavor violation (LFV) couplings of the Standard Model (SM) Higgs boson H with leptons from low energy experiments and the recent Compact Muon Solenoid experiment results, we investigate production of the SM Higgs boson associated with a lepton τ via eγ collision at the International Linear Collider (ILC) and Large Hadron Electron Collider experiments. The production cross sections are calculated and the LFV signals and the relevant SM backgrounds are examined. The LFV signals of the SM Higgs boson might be observed via eγ collision in future ILC experiments.